Determine the Factors Influencing the Investors' Participation to Adopt Takaful in Turkey (Global Journal of Management and Business Research, 2020)
In Muslim countries such as Turkey, it can be seen a rapid trend towards the Islamic financial instruments. The takaful system is alsosuch an instrument developed against the conventional insurance system and becoming widespread in Muslim countries. Therefore, this study aims to determine what the effective factors in people's participation in the takaful system in Turkey and have some implications for the increase in participation. In order achieve this goal, evaluations were carried out on a sample of 422 responders whose age were 18 and over and having salary. The responders were asked to respond about their socio-demographic characteristics such as gender, age, education level and their risk profiles. In addition, in order to reveal opinions of responders about the conventional and takaful system, self-administered survey questionnaire including 30 items based on five-point Likert scale were developed with reviewed literature studies and considering Turkish case.
Keywords: takaful (islamic insurance); factor; principal component analysis; binary logistic regression